Tailor-designed Oxalic Acid-Crosslinked Poly(vinyl alcohol)/Chitosan Biodegradable Films for Active Food Packaging Applications - Elaasar, Reem Hazem Fathy Anwar (AUC Knowledge Fountain, 2025)
Food packaging plastic waste is posing great threats to ecosystems, human health, and the planet's overall sustainability; therefore, research has been directed towards the fabrication of biodegradable food packaging materials. In this study, active and biodegradable oxalic acid (OA) crosslinked poly(vinyl alcohol) (PVA)/chitosan (CS) composite films of different weight ratios were synthesized via the solvent casting technique and their food packaging properties were investigated. Owing to its water resistance and antibacterial superiority, the composite film with the ratio of OA chemically crosslinked PVA/CS 80:20 was elected to be coated with green tea extract (GTE) to ameliorate its antibacterial and antioxidant activities. The chemical crosslinking of PVA by OA and the intermolecular hydrogen bonding between PVA and CS were confirmed by FTIR spectroscopy. Surface roughness of the composite films mainly determined their antibacterial activities. Interestingly, CS provided the composite films with higher mechanical strength and stiffness along with ultraviolet (UV) barrier and antibacterial properties. Despite reducing the water resistance, barrier properties and thermal stability of the composite films, the values are comparable to literature and the produced films are of a great potential for food packaging applications. Furthermore, GTE coating further augmented the active properties of the elected composite film yielding it quite applicable for active food packaging purposes.